The Narooma Terrane offshore: a new model for the southeastern Lachlan Orogen using data from rocks dredged from the New South Wales continental slope. Issue 1 (2nd January 2016) - Packham, G. H.; Hubble, T. C. T.
ABSTRACT: Eight dredges from the southern New South Wales continental slope sampled the offshore extension of the Lachlan Orogen. Two rock suites were recovered: (1) lower greenshist facies limestones, felsic volcanics, sandstones, mudstones and Moruya Suite granodiorite correlate with the onshore Silurian to mid-Devonian orogenic phase; and (2) a strongly deformed greenschist to lower amphibolite facies mafic volcanics, cherts, marbles, pelites and serpentinites correlate in part with the Cambro-Ordovician Wagonga Group of the Narooma Terrane. The mafic volcanic rocks have ocean island, tholeiitic and boninitic basalt affinities. The offshore distribution of ocean island basalt that correlates with medial Cambrian basalt breccias at Batemans Bay suggests a large seamount or seamount complex. The boninites, tholeiites and ultramafics could be part of a forearc-generated ophiolite. The Narooma Terrane basement is interpreted as the part of the bonititic arc postulated to have collided with Vandieland in late early Cambrian time. Mid-Cambrian rifting of the oceanward part of this arc remnant, generated the Albury–Bega Terrane oceanic basement exposed in the Howqua Valley in the west and Melville Point in the east. Overlying are upper–mid-Cambrian to lowermost Ordovician black shale and chert, Lower Ordovician to Gisbornian Adaminaby Group quartz turbidites and Gisbornian to lower Bolindian Bendoc Group black shales. Batemans Bay exposures are reinterpreted as a dismembered basin margin succession onlapping the west-facing attenuated flank of the Narooma Terrane. The Narooma Cambro-Ordovician cherts and mudstones were initially deposited outboard on the more elevated seamount flank elevated above the clastic-filled basin to the west. Benambran deformation commenced in latest Ordovician time uplifting the outer Narooma Terrane, shedding debris from the seamount and its flanks, culminating in allochthonous displacement of chert masses to the basin's eastern margin to Narooma, and emplacing them as a succession of thrust sheets. Contemporaneously, silt and mud of the Bogolo Formation, deposited from the west, were mixed with olistostomal basalt and chert debris from the east. Early Silurian westward tectonic transport of the Narooma Terrane ruptured the Albury-Bega basin floor at Batemans Bay, thrusting it and its sedimentary cover over its eastern margin as a series of thrusts each floored by melange (mapped Bogolo Formation), derived from the slope debris and its overpressured sedimentary cover. Offshore, the metamorphosed Benambran phase rocks are unconformably overlain by Tabberabberan cycle sediments and volcanics intruded by granodiorite. Our interpretation of the boundary between the Albury-Bega and Narooma terranes as a thrusted passive margin accumulation is incompatible with models of a Narooma Accretionary Complex formed by the subduction of the Paleopacific Plate.